2014
DOI: 10.1371/journal.pone.0092067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inclusion of Industry Trial Results Registries as an Information Source for Systematic Reviews

Abstract: BackgroundClinical trial results registries may contain relevant unpublished information. Our main aim was to investigate the potential impact of the inclusion of reports from industry results registries on systematic reviews (SRs).MethodsWe identified a sample of 150 eligible SRs in PubMed via backward selection. Eligible SRs investigated randomized controlled trials of drugs and included at least 2 bibliographic databases (original search date: 11/2009). We checked whether results registries of manufacturers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…The included studies fell into three categories: those which measured the numbers of studies reporting adverse events in published and unpublished sources (9 studies [ 16 , 23 , 25 , 27 , 30 , 34 , 35 , 40 , 43 , 44 ]), those which measured the numbers or types of adverse events in published and unpublished sources (13 studies [ 16 , 18 , 22 , 25 28 , 32 , 34 , 36 , 38 , 40 , 46 , 47 ]), and those which measured the difference in effect size of a meta-analysis with and without unpublished sources (11 studies [ 19 – 21 , 24 , 29 , 31 , 33 , 37 , 39 , 41 , 42 , 45 ]). There were 5 studies that contained data for more than one category.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies fell into three categories: those which measured the numbers of studies reporting adverse events in published and unpublished sources (9 studies [ 16 , 23 , 25 , 27 , 30 , 34 , 35 , 40 , 43 , 44 ]), those which measured the numbers or types of adverse events in published and unpublished sources (13 studies [ 16 , 18 , 22 , 25 28 , 32 , 34 , 36 , 38 , 40 , 46 , 47 ]), and those which measured the difference in effect size of a meta-analysis with and without unpublished sources (11 studies [ 19 – 21 , 24 , 29 , 31 , 33 , 37 , 39 , 41 , 42 , 45 ]). There were 5 studies that contained data for more than one category.…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 included studies reporting 28 meta-analyses that looked at magnitude of the pooled risk estimate—i.e., odds ratio or risk ratio for adverse events—with unpublished data and published data or a combination of published and unpublished data ( S4 Table ) [ 19 – 21 , 24 , 29 , 31 , 33 , 37 , 39 , 41 , 42 , 45 ]. Of these 28 meta-analyses, there were 20 instances where risk estimates were pooled for all published and unpublished studies as compared to published studies only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with other studies, showing that the search for unpublished trial data is still often lacking in systematic reviews. 24 25 26 29 30 In a random sample of 300 recent systematic reviews indexed in Medline in February 2014, only 19% reported searching trial registries. 31 A previous study by Hart in 2012 aimed to reanalyse meta-analyses by adding unpublished outcome data from trials obtained from the US Food and Drug Administration to published meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In einer komplexen Arbeit untersuchten Mitarbeiter des Instituts für Qualität und Wirtschaftlichkeit im Gesundheitswesen (IQWiG) 150 systematische Übersichtsarbeiten über 125 verschiedene Pharmaka auf den Einschluss von Daten aus Industrieregistern [13]. Auf den Einschluss von Registern hatten primär 133 Reviews verzichtet.…”
Section: » Keine Untersuchung Hat Bisher Den Nutzen Von Registern Belegtunclassified